Radiomics and Its Applications and Progress in Pancreatitis: A Current State of the Art Review - Yan, Gaowu; Yan, Gaowen; Li, Hongwei; Liang, Hongwei; Peng, Chen; Bhetuwal, Anup; McClure, Morgan A.; Li, Yongmei; Yang, Guoqing; Li, Yong; Zhao, Linwei; Fan, Xiaoping (Frontiers in Medicine, 2022)
Radiomics involves high-throughput extraction and analysis of quantitative information from medical images. Since it was proposed in 2012, there are some publications on the application of radiomics for (1) predicting recurrent acute pancreatitis (RAP), clinical severity of acute pancreatitis (AP), and extrapancreatic necrosis in AP; (2) differentiating mass-forming chronic pancreatitis (MFCP) from pancreatic ductal adenocarcinoma (PDAC), focal autoimmune pancreatitis (AIP) from PDAC, and functional abdominal pain (functional gastrointestinal diseases) from RAP and chronic pancreatitis (CP); and (3) identifying CP and normal pancreas, and CP risk factors and complications. In this review, we aim to systematically summarize the applications and progress of radiomics in pancreatitis and it associated situations, so as to provide reference for related research.